Silencing of PGK1 Promotes Sensitivity to Paclitaxel Treatment by Upregulating XAF1-Mediated Apoptosis in Triple-Negative Breast Cancer - Sun, Shanshan; Wu, Hao; Wu, Xiaohong; You, Zilong; Jiang, Yang; Liang, Xiaoshuan; Chen, Zhuo; Zhang, Ye; Wei, Wei; Jiang, Yongdong; Chen, Yanbo; Song, Yanni; et al. (Frontiers in Oncology, 2021)
Objective: Triple negative breast cancer (TNBC) is known to have aggressive clinical course and a high risk of recurrence. Given the lack of effective targeted therapy options, paclitaxel-based chemotherapy is still the primary option for TNBC patients. However, patients who fail to achieve a complete response during neoadjuvant chemotherapy may be mainly due to sensitivity and resistance to chemotherapy. Thus, we concentrated the present research on the role of PGK1 in the sensitivity to paclitaxel treatment and the possible underlying mechanisms in TNBC. Methods: After exposure to paclitaxel, a cell viability analysis was made to investigate the influence of PGK1 silencing on cell death. The effect of PGK1 on apoptosis induced by paclitaxel treatment was examined in vitro by flow cytometry cell apoptosis assays. Western blotting was performed to examine the impact of PGK1 on paclitaxel-induced apoptosis. The correlation of PGK1 with apoptosis-associated protein X-linked inhibitor of apoptosis (XIAP)-associated factor 1 (XAF1) was analyzed in 39 specimens by immunohistochemistry analysis. Results: We observed that silencing PGK1 sensitized triple-negative breast cancer (TNBC) cell lines to paclitaxel treatment as a result of increased drug-induced apoptosis. Furthermore, mechanistic investigations suggested that XAF1 was increased in PGK1-knockdown cells along with the expression of the apoptotic proteins including cleaved caspase-3 and Bax. Immunohistochemistry analysis showed that PGK1 was negatively related to XAF1. Moreover, we found that downregulation of XAF1 reduced paclitaxel-induced apoptosis in PGK1-silenced triple-negative cell lines. Conclusion: Our results identified PGK1 as a potential biomarker for the treatment of TNBC, and inhibition of PGK1 expression might represent a novel strategy to sensitize TNBC to paclitaxel treatment.